The Outsourcing Decision: How to Reap Benefits And Prevent against Associated Drawbacks - Efue, Barbara (2010)
Firms are constantly faced with the dilemma of trying to decide whether or not to outsource non-core business activities; in simple terms, the options to either rely on in-house resources or utilize external resources. This may be due to uncertainties that arise as a result of the numerous benefits and drawbacks of outsourcing that continue to be proposed by various schools of thought. This aim of this report is to identify some factors that if considered, could minimise these uncertainties as well indicate how the benefits of outsourcing may be achieved and the pitfalls or drawbacks avoided. In establishing these factors, a systematic approach has been undertaken. Recent trends that have resulted in the popularity of the outsourcing concept are discussed, different types of outsourcing are explained and arguments for and against outsourcing (which incorporate potential benefits and drawbacks) have been examined. The research goes a step further in that it identifies a number of outsourcing strategies that firms can choose from. It is important to state here that this report is an off- shoot from an initial research that was focused on identifying the business activities passionate small and medium sized enterprises (SMEs) would be willing to outsource to a business process outsourcing (BPO) company. (Please refer to group report). In that report, a few drivers of outsourcing were identified. This report however explores the concept in more detail and more comprehensively. In addition, the scope of this research broadens from just being limited to passionate SMEs to one that takes into all types of firms in general, regardless of size. For the methodology, a combination of structured interviews (Please refer to group report) and an extensive review of literature via academic journals and articles have been undertaken in order to develop a framework. The research findings indicate that outsourcing like any other business tool has its potential pros and cons. However, benefits can be maximised if the decision results from extensive strategic analysis; as well as if firms are able to properly manage and monitor the process.